An Analysis of Translation Techniques of Modality in Hortatory Text by English Department Students of UNP - Yoza Rahmadani; Rusdi Noor Rosa (Universitas Negeri Padang, 2021)
This study aims at finding out the translation techniques of modality made by the third year English Department students of Universitas Negeri Padang in trahslating hortatory text. This study used a descriptive method. The data were the translation of hortatory text entitled Bersama Atasi Covid-19 done by the third year English Department Students of Universitas Negeri Padang. The data were collected by using a test and were analyzed using the translation technique of modality which literal translation technique is the technique frequenlty used by the students in their translation with the frequency of 255 data (74,12%). Established Equivalence and Linguistic Compression (7.0%) are the second most frequent of translation techniques of modality used. Linguistic Amplification (6.68%), and the last is Reduction that is used 18times with (5.2%) percentage.